2020
DOI: 10.1089/fpsam.2020.0029
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Roof Fractures: An Evidence-Based Approach

Abstract: Importance: There is controversy surrounding the management of orbital roof fractures. Guidelines with regard to when to operate and type of reconstruction are lacking. Categorizing these data will help clinicians make informed decisions about the management of orbital roof fractures and avoid preventable complications.Objective: To perform a systematic review evaluating underlying causes, associated complications, and management of orbital roof fractures including reconstructive options in the general populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 61 publications
0
12
0
2
Order By: Relevance
“…Orbital roof fractures typically do not require operative intervention as these rarely have significant displacement. Lucas et al [28] published a systematic review on management of orbital roof fractures. Although the study included both adult and pediatric populations, they found that pediatric populations were more frequently treated with conservative management [28].…”
Section: Orbital Roofmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbital roof fractures typically do not require operative intervention as these rarely have significant displacement. Lucas et al [28] published a systematic review on management of orbital roof fractures. Although the study included both adult and pediatric populations, they found that pediatric populations were more frequently treated with conservative management [28].…”
Section: Orbital Roofmentioning
confidence: 99%
“…Lucas et al [28] published a systematic review on management of orbital roof fractures. Although the study included both adult and pediatric populations, they found that pediatric populations were more frequently treated with conservative management [28]. This was further supported in a review published by Sandhu et al [29 ▪ ] with reported operative intervention rates ranging from 6 to 18%.…”
Section: Orbital Roofmentioning
confidence: 99%
“…In a systematic review by Lucas et al, most orbital roof fractures were noncomminuted and thus managed expectantly, with close follow-up examinations and reimaging for new or worsening symptoms. 25 It is important to note that if left untreated, displaced supraorbital fractures can result in a fixed deformity with significant diplopia that cannot be fully corrected. Therefore, follow-up often includes more long-term evaluation compared with other patterns to avoid missing a progressive deformity.…”
Section: Orbital Roof Fracturesmentioning
confidence: 99%
“…The transconjunctival approach is often used for orbital fractures to minimize risk of external scar, ectropion, and eyelid retraction; however, a transcutaneous incision may be required in complex cases needing greater visualization. 25 Iliac, rib, or skull donor sites can be used for autogenous orbital reconstruct in immature calvarium when the absence of a calvarial diploe space prevents harvesting split calvarial grafts, a pericranial shave graft can be harvested with a sharp osteotome (►Fig. 5).…”
Section: Orbital Trapdoor Fracturesmentioning
confidence: 99%
“…Complications of surgical interventionmost frequently, longstanding diplopia, persistent enophthalmos, ectropion and, most concerning, vision loss-underscore the importance of establishing consistent findings that warrant surgical intervention. 6 Despite many studies examining the management of various isolated and combination orbital wall fractures, [10][11][12] an algorithm for treatment using ophthalmologic exam and CT findings has yet to be established for eyes in the setting of orbital fractures broadly. This study examines orbital fractures at a level I trauma center for clinical and imaging findings to guide patient stratification into conservative follow-up, medical treatment, and/or surgical management approaches.…”
mentioning
confidence: 99%